2017
DOI: 10.1039/c6qi00300a
|View full text |Cite
|
Sign up to set email alerts
|

G-quadruplex DNA targeted metal complexes acting as potential anticancer drugs

Abstract: This review summarizes the recent development of G4 DNA targeted metal complexes and discusses their potential as anticancer drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
169
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(171 citation statements)
references
References 136 publications
2
169
0
Order By: Relevance
“…A subclass of this type of G4 DNA binders are metal complexes containing at least one planar face (i.e. square planar or square‐based pyramidal complexes) . Metal complexes with these geometries have demonstrated to be particularly well suited as G4 binders since the electropositive metal withdraws electron density from the planar ligand making it more suitable for π–π stacking with the guanine tetrad.…”
Section: Introductionmentioning
confidence: 99%
“…A subclass of this type of G4 DNA binders are metal complexes containing at least one planar face (i.e. square planar or square‐based pyramidal complexes) . Metal complexes with these geometries have demonstrated to be particularly well suited as G4 binders since the electropositive metal withdraws electron density from the planar ligand making it more suitable for π–π stacking with the guanine tetrad.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, most G‐quadruplex binding molecules were based on organic heteroaromatic compounds . Subsequently, it was shown that metal complexes can also be excellent G4 DNA binders thanks to their unique electronic and structural features, as has been discussed in detail elsewhere . An example of this, are metal salphen and salen complexes, which have been extensively studied over the past 10 years (see Figure ) .…”
Section: Introductionmentioning
confidence: 99%
“…The interaction with the G‐quadruplex grooves and loops is also taken into account for improving the selectivity for G‐quadruplex versus duplex DNA. Among the compounds able to target G‐quadruplexes, a number of metal complexes bearing aromatic ligands have been reported, including those of porphyrin, salphens, and salophens . In this context, we have designed a new extended planar ligand, based on a pyrazine core, namely dipyrazino[2,3‐ a :2′,3′‐ h ]phenazine (dph; Figure a).…”
Section: Introductionmentioning
confidence: 99%